Creating Memorable Stays: How Customer Experience Drives Delight In The Hotel Sector - Adi, Antonius (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2025)
In the increasingly competitive hospitality industry, customer experience has become a strategic element in building competitive advantage. This study aims to examine the effect of customer experience on customer delight, a condition in which customers feel satisfaction that exceeds their expectations. A quantitative approach was employed using a causal research design and data were collected through a survey of 100 guests at 3- to 5-star hotels in Indonesia. Data analysis was conducted using Structural Equation Modeling with SmartPLS 4. The results indicate that customer experience has a positive and significant effect on customer delight. These findings suggest that customer experience significantly and positively influences customer delight. This study provides theoretical contributions by strengthening the relationship between experience and delight in the service context and offers practical implications for hotel managers in designing services that prioritize customer experience.